Optimal volt/var control of distribution system using MOPSO - Ramesh Babu M; C. Venkatesh Kumar; R. Sreekanth (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents a novel method for solving multi-objective Volt/Var control of radial distribution system. The Volt/Var control is formulated as a multi-objective optimization problem which consists of the following objectives: minimization of real power loss, minimization of total voltage deviation and minimization of number of OLTC’s and capacitor operation and voltage fluctuations for a day-a-head in Distribution system.The Proposed MOPSO Algorithm is used to find the optimal settings of control variables such as On-Load tap changer (OLTC) and Shunt Capacitor. The proposed MOPSO algorithm is tested on a standard IEEE33-bus and 69-bus distribution system.